AGROLANCE: REPRESENTATION OF GROWTH BALANCE OF TOMATO PLANTS IN DRY LAND IN THE CONTEXT OF A DANCE WORK - Damanik, Desy Wulan Pita Sari; Alfassabiq Khairi (International Journal of Educational Research Excellence (IJERE), 2023)
Agrolance dance work is representation of research results entitled " Combination of Bio-Organo- Minirel Fertilizers on Optimizing the Growth and Production of Tomatoes (Salanum Lycopersicum) In Dryland Environment " (2023) by Alfassabiq Khairi in the journal Agricultural Sciences which is research and concept ideas from this work. Through this creative study, the analogy that appears in each part of Agrolance's work is described to show the growth balance of tomato plants and fertilizer on dry land on the bodies of beginner dancers which is answered based on the experiences of the dancers' bodies through several weeks of experimentation to see the results of their bodies. This research also provides insight into interdisciplinary research in dance and science agriculture . These findings have important implications in today's arts and agriculture context, which faces challenges in creating inclusive spaces, scientific collaboration, and discovering experimental results. This research uses a case study method with a choreographic approach. Using a qualitative descriptive research method means getting data qualitatively, then writing it descriptively. The author, as the main instrument in this research, collected data by means of participant observation, unstructured interviews, and through dance work documents. In this work, the dancer is analogous to dry land, the movements produced by the dancer are the results of the tomato plant, organic fertilizer is consumption and daily activities carried out, and inorganic fertilizer is body exercise, taste exercise, bodily experience given by the choreographer to the dancer. The creation method in this work uses the exploration method as the initial part in developing the creativity of the creation process, improvisation to find movements by chance or spontaneously, composition to arrange the movements that have been obtained, as well as periodic corrective evaluation of the process.